2006
DOI: 10.12968/bjon.2006.15.sup1.20687
|View full text |Cite
|
Sign up to set email alerts
|

Treating a pressure ulcer with bio-electric stimulation therapy

Abstract: Mr Jones lived independently until he developed necrotic pressure ulcers over his heels and could no longer mobilize to care for himself. He was transferred to a nursing home where he lived for 18 months and where the nurses could care for his wounds. The wound had been on his right heel without changing over the 18 months and, although attempts to hydrate the eschar had been somewhat successful, the necrotic tissue proved stubborn creating large quantity of fibrous slough. Mr Jones was initially assessed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…However, since CDC flows for 1 s or longer, at sufficiently high amplitudes, caustic alkaline (NaOH and H 2 ) and acid (HCl) products may form at the cathode and anode, respectively, which may cause observable tissue irritation. CDC studies that are applied between 200 and 800 lA have been reported to have positive wound-healing outcomes in seven clinical trials, of which three are case studies [23][24][25][26][27][28][29] Wolcott et al 24 reported that after failure of SWC to effect measurable progress toward healing, of 75 ischemic skin ulcers treated with CDC over 15 weeks, 40% closed in a mean of 9.6 weeks; while the healing rate for all wounds was 13.4% per week. Gault and Gatens 25 used CDC and the same protocol as Wolcott et al 24 to treat 100 chronic ulcers of the integument that were deemed recalcitrant to SWC.…”
Section: Direct Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since CDC flows for 1 s or longer, at sufficiently high amplitudes, caustic alkaline (NaOH and H 2 ) and acid (HCl) products may form at the cathode and anode, respectively, which may cause observable tissue irritation. CDC studies that are applied between 200 and 800 lA have been reported to have positive wound-healing outcomes in seven clinical trials, of which three are case studies [23][24][25][26][27][28][29] Wolcott et al 24 reported that after failure of SWC to effect measurable progress toward healing, of 75 ischemic skin ulcers treated with CDC over 15 weeks, 40% closed in a mean of 9.6 weeks; while the healing rate for all wounds was 13.4% per week. Gault and Gatens 25 used CDC and the same protocol as Wolcott et al 24 to treat 100 chronic ulcers of the integument that were deemed recalcitrant to SWC.…”
Section: Direct Currentmentioning
confidence: 99%
“…This is unfortunate, as CDC comes close to mimicking the physiological DC EF that occurs after wounding of the integument and subcutaneous tissues. Interestingly, a relatively new bioelectric wound dressing that contains a miniature electric circuit which delivers micro-amperage CDC has been used with some reported success for treating pressure and venous ulcers in the United Kingdom 28,29 (Fig. 3).…”
Section: Direct Currentmentioning
confidence: 99%
“…Electrical stimulation has also reported to have no induce on wound healing [125], while in other studies electrical stimulation was shown to enhance the rate of pressure ulcer healing compared unstimulated controls [126] However, due to the great differences in the methodologies of electrical stimulation, and differences in electrical field forces used, from weak to high-voltage pulsed galvanic stimulation, and the small numbers of participants involved in most studies, further work is required to determine the validity of electrical stimulation in eliminating pressure ulcers.…”
Section: Electrical Stimulationmentioning
confidence: 97%
“…Several reports document the benefits and safe application of EST on specific cases with very challenging wounds 6,[64][65][66][67][68][69][70][71][72][73][74][75][76][77] and other noncontrolled retrospective 78,79 and prospective research designs. [80][81][82][83][84][85] Two of the original clinical reports are often identified as controlled studies since they included a relatively large number of subjects; however, they compared healing outcomes produced after EST to only six patients with bilateral wounds.…”
mentioning
confidence: 99%
“…28,35,38,40,41,46,47,50,53,58,60 Research that focused on pressure ulcer treatment using EST is most common. A total of 27 clinical reports evaluated the effect of EST on people with pressure ulc ers, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]64,67,[69][70][71]74,75,77,79,82,[85][86][87] and 17 of these were controlled clinical trials. [28][29][30][31][32][33][34][35][36][37]…”
mentioning
confidence: 99%